DEKONSTRUKSI PINJAMAN DAN PEMBIAYAAN BISNIS SYARIAH: ANALISIS KRITIS TERHADAP PRINSIP DAN PRAKTIK (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
The rapid development of the Islamic finance industry reflects the growing demand for financial systems that adhere to Islamic principles, such as the avoidance of riba (interest), gharar (uncertainty), and maysir (speculation), as well as the promotion of social justice and public welfare. However, in practice, the implementation of Islamic financing continues to face serious challenges, particularly the gap between the normative concepts of Islamic economics and the operational realities of Islamic financial institutions. This paper aims to analyze and deconstruct the practices of loans and financing in Islamic business, focusing on the extent to which Islamic financing products truly reflect the social justice values that form the core objectives of Islamic economics. This study employs a library research method using a qualitative, descriptive-analytical, and critical approach. Data were collected from various literature sources, including books, academic journal articles, research reports, and relevant policy documents related to Islamic financing. The analysis was conducted through thematic categorization, content analysis, and a deconstructive approach to reveal contradictions between theory and practice in Islamic financing. The findings indicate that several Islamic financing products, such as murabaha, mudharabah, and musyarakah, in practice often exhibit characteristics similar to those of conventional financial systems, particularly in terms of profit margins and imbalanced risk-sharing mechanisms. This condition has the potential to create injustice, especially for small-scale customers and micro-enterprises. Therefore, strengthening regulatory frameworks, improving Islamic financial literacy, fostering product innovation, and enhancing transparency are essential to ensure that Islamic financing goes beyond symbolic compliance and genuinely embodies the goals of social justice and societal welfare.